Contemporary Sociological Theory (III) - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2010)
The aim of this essay is to identify and critically assess the key concepts, ideas, epistemological principles, and the relational – symmetric and asymmetric – aspects of the ongoing global division of sociological labor. The third part of the essay attempts to explore the ambivalent relations between the ‘global’ content and ‘national’ form of public sociology. There are four dilemmas that confront Michael Burawoy in his attempts to articulate the idea of public sociology in a globalising context: first, the contradiction between the universal content and national form of public sociology; second, the contradiction between analytical realism and pluralist relativism; third, the (nominal) contradiction between artificial types of public sociology and critical sociology; fourth, the contradiction between epistemological pluralism and value pluralism. The conclusion is that, despite the excessively ethnocentric principles of so-called ‘methodological nationalism’, it is precisely the claim to more cosmopolitan sociological principles that makes an overly ‘national’ form of public sociology ‘global’. The main task is to ensure the ongoing power of public sociology to make global sociological discourse negotiable. What is needed in public sociology is not another symmetric-functional historicism, but a deeper critical understanding of both analytical theoretical frameworks and normative discourses, including the attempts to understand the unevenly distributed global sociological field of asymmetric institutional and intellectual power relations.
Keywords: public sociology; critical sociology; professional sociology; methodological nationalism; global division of sociological labour